120 (???)
2007-02-25 07:03:57
·
answer #1
·
answered by dippidappi 2
·
0⤊
1⤋
Its roots are (2 +- Sqrt[4 + 4(5)(12)])/10
= (2 +- Sqrt[244])/10 = (2 +- 2Sqrt[61])/10
= (1 +- Sqrt[61])/5. Hence, we can factor as follows:
5x^2 - 2x - 12 = (x - (1 + Sqrt[61])/5)(x + (1 - Sqrt[61])/5).
2007-02-25 14:55:26
·
answer #2
·
answered by I know some math 4
·
0⤊
0⤋
5(x^2) - 2x - 12
consider a(x^2)+bx+c=0
then x= [-b+-sqrt(b^2-4ac) }/2a
Using that we can write,
5(x^2) - 2x - 12 = {x - [ (1+ sqrt61) ]/5 ] } {x - [ (1- sqrt61) ]/5 ] }
2007-02-27 13:03:38
·
answer #3
·
answered by hirunisha 2
·
0⤊
0⤋
Prime
2007-02-25 14:57:03
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
5squared- 2x- 12
2007-02-25 14:57:52
·
answer #5
·
answered by J D 1
·
0⤊
1⤋
5x^2-2x-12
x=-(-2)+/-[sq.rt(4+240)]/10
=[2+/-rt(244)]/10
2007-02-25 14:56:25
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
does anyone go to school what have we all turned to drop outs
2007-02-25 14:53:40
·
answer #7
·
answered by nightfallsid 2
·
0⤊
2⤋